2017
DOI: 10.3389/fnagi.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Focal Connectivity Deficits in Alzheimer's Disease Using Directional Brain Networks Derived from Resting-State fMRI

Abstract: Connectivity analysis of resting-state fMRI has been widely used to identify biomarkers of Alzheimer's disease (AD) based on brain network aberrations. However, it is not straightforward to interpret such connectivity results since our understanding of brain functioning relies on regional properties (activations and morphometric changes) more than connections. Further, from an interventional standpoint, it is easier to modulate the activity of regions (using brain stimulation, neurofeedback, etc.) rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 116 publications
0
11
0
Order By: Relevance
“…Other methods such as Granger Causality can identify directional functional interactions, whereby activity in one region precedes activity in another. Using this method, one study identified the LC as the node of functional connectivity deficits in AD patients ( Zhao et al, 2017 ). These deficits were shown to culminate in the orbitofrontal cortex, taking multiple routes through the working memory, emotional memory, and language system circuits.…”
Section: Human Studiesmentioning
confidence: 99%
“…Other methods such as Granger Causality can identify directional functional interactions, whereby activity in one region precedes activity in another. Using this method, one study identified the LC as the node of functional connectivity deficits in AD patients ( Zhao et al, 2017 ). These deficits were shown to culminate in the orbitofrontal cortex, taking multiple routes through the working memory, emotional memory, and language system circuits.…”
Section: Human Studiesmentioning
confidence: 99%
“…The LC undergoes early and significant deterioration and recent imaging studies suggest LC functional dysconnectivity that involves brain regions other than the hippocampus in AD. A recent work employed Granger causality mapping to create a model of directed connectivity and characterized regional functional coupling in AD and healthy controls (Zhao S. et al, 2017 ). With group differences determined with a generative model of pathology, the authors identified the LC and right orbitofrontal cortex as the two foci of disruption in AD.…”
Section: Noradrenergic Dysfunction In Ad and Pdmentioning
confidence: 99%
“…Decreased volume, cell loss and aggregation of tau protein in the LC of Alzheimer's disease (AD) patients have been widely reported . Resting‐state functional MRI revealed that 2 foci, the LC and orbitofrontal cortex, were affected in AD . The connectivity between the LC and parahippocampal gyrus was reduced in patients with MCI due to AD compared with that in healthy controls .…”
mentioning
confidence: 99%